ДО 75-РІЧЧЯ ІНСТИТУТУ ЗАХИСТУ РОСЛИН НААН УКРАЇНИ. ЕНТОМОЛОГІЧНІ ШКОЛИ - Krut’, M. V. (public organization "Ukrainian Entomological Society", I.I. Schmalhausen Institute of Zoology of National Academy of Sciences of Ukraine, Institute of Plant Protection of National Academy of Agrarian Sciences of Ukraine, 2021)
he entomological schools were formed in the Institute of Plant Protection of NAAS of Ukraine by carrying out of scientific investigations on decision of the major questions of crop protection. The followers of Academician of NASU V.P. Pospelov carried out complex of the works on studying of insects’ pathology for grounding microbiological and chemical methods of insect pests’ control. The direction of scientific investigation of Professor’s M.A. Telenga school was using of biological methods on limitation of number of crops insect pests. His followers M.P. Dyadechko and V.P. Prystavko created their scientific schools too. Z.S. Golovyanko was at the head of the school of forest entomologists (D.F. Rudnev and other). Further Professor D.F. Rudnev worked out chemical method of pest organisms’ control, but revealed the alternative to it — the using of the resistant plants’ varieties to insect pests. Professors V.A. Sanin and V.P. Smilyanets followed his legacy. The weighty results of investigation of Academician’s of NASU V.P. Vasyliyev school are theoretical grounding of economical expediency of insecticides’ application and working out of the basis of plant integrated protection. The main part of activity of Professor B.A. Areshnikov and his followers was devoted to work on scientific grounding of grain crops’ effective and ecologically safe protection from insect pests, in particular corn bug. The scientists-entomologists were prepared by Ph.D, Professors V.G. Dolin (on questions of the forecasting of insect pests’ development in plants and a grounding of effective control measures), M.P. Sekun (on pesticides’ toxicology), V.M. Chayka (on forecast and ecology) and candidates of biological sciences N.V. Lappa (on microbiological method of plant protection), V.P. Omeluta (on plant quarantine) too. Some representatives of scientific schools of Academician of NAAS V.P. Fedorenko and Professor S.O. Trybel’ on direction of ecological and economical optimization of plant integrated protection from insect pests are in the Institute. In some periods of time Ye.V. Zverezomb-Zubovsky, V.P. Vasyliyev and V.G. Dolin were at the head of Ukrainian Entomological Society. V.P. Fedorenko is a president of this public organization to this day.